Cinderella Gets an Invitation: recognising and organising systems maintenance and support - Bacon, C. James (Australasian Journal of Information Systems, 1993)
Systems maintenance of existing systems is a ’Cinderella’ subject in the field of information systems & technology (1ST). Although it accounts for the majority of systems work, the subject is generally neglected and taken for granted. Based on studies carried out in a large Australasian organisation, evidence is presented for recognising the strategic role of systems maintenance, as a complement to new development. Alternative means of organising systems development work is examined, with the conclusion that a separate systems support group for carrying out maintenance may have net advantage. A re-definition of maintenance, according to a taxonomy of eight different types, is proposed. Effective methodology and metrics for maintenance are also addressed, together with the general phenomenon of "entropological deterioration’, and 12 factors that need to be used in assessing existing systems.